Obesity Does Not Affect Patient-Reported Outcomes following Patellofemoral Arthroplasty - Tishelman, Jared C.; Pyne, Abigail; Kahlenberg, Cynthia A.; Gruskay, Jordan A.; Strickland, Sabrina M. (The Journal of Knee Surgery, 2020)
Patellofemoral arthroplasty (PFA) has garnered attention in recent years as an effective alternative to total knee arthroplasty for patients with symptomatic, isolated patellofemoral joint arthritis. Obesity has previously been identified as a risk factor for revision surgery, but its effect on patient-reported outcome measures (PROMs) has not been evaluated. A retrospective review of a consecutive series of PFA surgeries was conducted at a single, specialized orthopedics center in a major urban center. Patients were dichotomized by body mass index (BMI) as obese (O, BMI >30) or nonobese (NO, BMI: 18.5–25). Demographic, surgical information, and PROMs were collected and analyzed accordingly. Seventy-six patients (41 nonobese, 35 obese) were identified. Patients who were obese presented with significantly worse preoperative PROMs regarding knee-specific quality of life, physical function, and MH or mental health (knee injury and osteoarthritis outcome score quality of life [KOOS QoL], NO: 26.2, O: 14.7, p = 0.019; KOOS PF, NO: 38.2, O: 50.5, p = 0.002; Veterans Rand-12 mental health [VR-12 MH], NO: 54.2, O: 47.0, p = 0.033). No significant difference was seen in improvement in knee function scores between patients who were obese or nonobese (KOOS QoL, NO: 39.5, O: 40.6, p = 0.898; KOOS PS [physical function], NO: –17.8, O: –17.3, p = 0.945). Additionally, no difference in the rate of PFA revision was observed and there were no postoperative complications reported. Obese patients with isolated PFA can expect the same improvement in function as nonobese patients following patellofemoral joint arthroplasty. This paper underscores the priority of patient selection in PFA and challenges the notion that surgeons should exclude patients from receiving a PFA on the basis of obesity.
Keywords: patient-reported outcomes; patellofemoral arthroplasty; obesity